Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1093/ajcn/58.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium and bone density among middle-aged and elderly women in China

Abstract: Associations between dietary calcium and bone status were investigated in 843 Chinese women aged 35-75 y who were selected from five rural counties where dietary calcium varied considerably. Bone mineral content (BMC) and bone mineral density (BMD) at the radius were significantly higher in one of the pastoral counties with higher calcium intake than in the nonpastoral counties. Analysis by individual for all counties combined showed that BMC and BMD were correlated positively with total calcium (r = 0.27-0.38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(46 citation statements)
references
References 49 publications
3
41
0
2
Order By: Relevance
“…Details of the survey, including subject selection, dietary survey, health and lifestyle questionnaire, and blood collection techniques, have been described previously (Hu et al, 1993a(Hu et al, ,b, 1994a. In summary, ®ve counties were chosen from among the original 65 that participated in our 1983 ecological survey in rural China (Chen et al, 1991).…”
Section: Sampling Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the survey, including subject selection, dietary survey, health and lifestyle questionnaire, and blood collection techniques, have been described previously (Hu et al, 1993a(Hu et al, ,b, 1994a. In summary, ®ve counties were chosen from among the original 65 that participated in our 1983 ecological survey in rural China (Chen et al, 1991).…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…The intake of foods and food ingredients was determined in the 3-day weighed food dietary survey (Hu et al, 1993a(Hu et al, , 1994b. Before each meal, investigators ®rst separated and weighed selected foods for each subject.…”
Section: Dietary Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Dairy consumption in Chinese populations is low but milk is potentially of benefit for bone health. 4 The recommended minimum daily requirement for calcium in Chinese women is set at 1000 mg/day 5 but several studies report intakes as low as 230-724 mg/day 1,6,7 and higher dietary calcium intake was associated with higher bone mass. 7 A study in Chinese women living in Hong Kong showed that bone loss can be reduced by supplementing with 800 mg calcium per day using fortified milk.…”
Section: Introductionmentioning
confidence: 99%
“…4 The recommended minimum daily requirement for calcium in Chinese women is set at 1000 mg/day 5 but several studies report intakes as low as 230-724 mg/day 1,6,7 and higher dietary calcium intake was associated with higher bone mass. 7 A study in Chinese women living in Hong Kong showed that bone loss can be reduced by supplementing with 800 mg calcium per day using fortified milk. 8,9 Similarly, a study in Chinese women in Malaysia showed that supplementing with 1200 mg calcium per day from fortified milk significantly reduced the percentage of total body bone loss compared to the control group.…”
Section: Introductionmentioning
confidence: 99%